2022
DOI: 10.3390/su14020649
|View full text |Cite
|
Sign up to set email alerts
|

Cost Estimations of Water Pollution for the Adoption of Suitable Water Treatment Technology

Abstract: This study analyzed the cost implications of using suitable technologies and the cost of inaction when addressing water pollution. This was achieved by developing three main models for the costs (model one) and benefits (model two and model three). The first model accounts for the operational costs of adopting suitable technologies, namely the use of diatomaceous earth for textile wastewater treatment. The second model analyzed the cost of inaction through analyzing the cost of treatment for water pollution-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It was found that around 2.2 million people die each year due to the consumption of polluted water [123]. The cost of treating waterborne diseases around the world is approximately USD 7.3 million [124]. At least 2 billion people utilize polluted water sources worldwide.…”
Section: Water Treatmentmentioning
confidence: 99%
“…It was found that around 2.2 million people die each year due to the consumption of polluted water [123]. The cost of treating waterborne diseases around the world is approximately USD 7.3 million [124]. At least 2 billion people utilize polluted water sources worldwide.…”
Section: Water Treatmentmentioning
confidence: 99%
“…This complicated process relies greatly on the data that are collected and sent by sensor nodes, which shows the importance of WSNs in this IoT application (i.e., water monitoring system). According to Mumbi and Watanabe [ 18 ], water pollution cost is significantly high, and it may have other effects, such as health and environmental crises. It can be seen from the above example that WSNs play a crucial role in controlling key operations in IoT applications.…”
Section: Background and Challengesmentioning
confidence: 99%
“…The growing concern over water pollution and deteriorating water quality, particularly among policymakers, is underscored by global statistics: an estimated one billion people lack access to safe drinking water, while 2.5 billion lack adequate sanitation facilities. As a consequence of these insufficient sanitation resources worldwide, around 4 billion cases of waterborne diseases are reported annually, a major contributor to fatalities, notably among children under 5 years old [3,4]. Richards et al [5] investigated emerging organic contaminants (EOCs) in the Ganges River, India, focusing on industrial clusters where untreated wastewater from factories contaminates rivers and groundwater.…”
Section: Introductionmentioning
confidence: 99%